PENGARUH KUALITAS PELAYANAN, KEPERCAYAAN DAN KUALITAS PRODUK TERHADAP KEPUASAN ANGGOTA (Studi Kasus pada KSPPS BMT AL FATAA Ulujami Kabupaten Pemalang) - Nurhidayah, Evinta Amalia; Santoso, Nanda Joko; Ernawati, Fidyah Yuli (Sekolah Tinggi Ilmu Ekonomi Semarang, 2025)
Member satisfaction reflects the level of a person's feelings after comparing expectations with the performance of services received, which in turn encourages the creation of long-term loyalty and attachment to the institution. This study aims to determine the influence of service quality, trust, and product quality on member satisfaction at KSPPS BMT AL FATAA Ulujami, Pemalang Regency. The population in this study consists of members of KSPPS BMT AL FATAA Ulujami, Pemalang Regency, with a sample of 100 members. The sampling technique used is nonprobability sampling with a purposive sampling approach. The analytical tools employed in this study include instrument testing (validity and reliability tests), descriptive statistical analysis, classical assumption tests (normality, multicollinearity, heteroscedasticity, and autocorrelation tests), model feasibility test, multiple linear regression analysis, and hypothesis testing through t-tests and F-tests. The results indicate that the service quality variable (X1) has a t value of 5.803 > t table 1.985 and a significance value of 0.000 < 0.05, indicating a significant effect on member satisfaction (Y). The trust variable (X2) has a t value of 4.734 > t table 1.985 and a significance value of 0.000 < 0.05. The product quality variable (X3) has a t value of 4.763 > t table 1.985 and a significance value of 0.000 < 0.05. Based on the results of the F-test (model feasibility test), the calculated F value is 46.843, which is greater than the F table value of 3.09, with a significance level of 0.000 < 0.05. This indicates that the variables of service quality, trust, and product quality are appropriate to be used as research model variables. The coefficient of determination (Adjusted R Square) is 0.581 which means that 58.1% of member satisfaction can be explained by the variables of service quality, trust, and product quality. The remaining 41.9% is influenced by other factors not included in this study. The conclusion of this study is that service quality has a positive and significant effect on member satisfaction at KSPPS BMT AL FATAA Ulujami, Pemalang Regency. Trust also has a positive and significant effect on member satisfaction. Likewise, product quality has a positive and significant effect on member satisfaction. Collectively, service quality, trust, and product quality have a positive and significant effect on member satisfaction. Suggestion based on the research findings indicates that KSPPS BMT AL FATAA Ulujami, Pemalang Regency, is advised to improve service quality, maintain the consistency and integrity of its staff, and develop more flexible products tailored to the members' needs, thereby enhancing member satisfaction.